A case of metastatic epithelioid hemangioendothelioma of the mandible. Issue 4 (July 2022) - Tasaki, Takako; Ohba, Seigo; Ogata, Kinuko; Katase, Naoki; Asahina, Izumi
Abstract: Epithelioid hemangioendothelioma (EHE) is a rare non-epithelial tumor derived from vascular endothelial cells. A 70-year-old Japanese man was diagnosed with metastatic EHE of the mandible, which originally developed at the superior vena cava (SVC). He was already under best supportive care and intraoral care for pain relief and to maintain his quality of life due to multiple metastases of EHE to the lung and liver. He was able to maintain oral nutrition until right before passing away, 24 months after his first visit.